An Enhanced Cloud Based Environment for Big Data Analytics in Health Care - Senthil Kumar, S.; Mythili, S. (Asian Journal of Science and Applied Technology, 2018)
Today, one of the promises of the growing critical mass of clinical data collection in electronic health record (EHR) systems is secondary use (or re-use) of the data for other purposes, such as quality enhancement and clinical research. The growth of such data is increasing dramatically in recent years. The analysis of the above data is usually called analytics (or data analytics).